2019
DOI: 10.3389/fmicb.2019.01655
|View full text |Cite
|
Sign up to set email alerts
|

Fecal and Mucosal Microbiota Profiling in Irritable Bowel Syndrome and Inflammatory Bowel Disease

Abstract: An imbalance in the bacterial species resulting in the loss of intestinal homeostasis has been described in inflammatory bowel diseases (IBD) and irritable bowel syndrome (IBS). In this prospective study, we investigated whether IBD and IBS patients exhibit specific changes in richness and distribution of fecal and mucosal-associated microbiota. Additionally, we assessed potential 16S rRNA gene amplicons biomarkers for IBD, IBS, and controls (CTRLs) by comparison of taxonomic composition. The relative abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
142
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(157 citation statements)
references
References 79 publications
13
142
0
2
Order By: Relevance
“…To better explore the difference between dietary fibers and prebiotics, it is important to remark that human enzymes are not able to degrade several glyosidic linkages present in a subset of polysaccharides, such as cellulose, hemicelluloses, mucilage, pectin and lignin, and those not digested by human enzymes are often partly fermented in the gastrointestinal tract [20]. Some dietary fibers are also able to selectively stimulate the growth and/or activity of intestinal bacteria potentially associated with health and well-being, acting as prebiotics [10].…”
Section: Prebiotics and Dietary Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…To better explore the difference between dietary fibers and prebiotics, it is important to remark that human enzymes are not able to degrade several glyosidic linkages present in a subset of polysaccharides, such as cellulose, hemicelluloses, mucilage, pectin and lignin, and those not digested by human enzymes are often partly fermented in the gastrointestinal tract [20]. Some dietary fibers are also able to selectively stimulate the growth and/or activity of intestinal bacteria potentially associated with health and well-being, acting as prebiotics [10].…”
Section: Prebiotics and Dietary Fibersmentioning
confidence: 99%
“…As gut microbiota have been involved in the pathogenesis of several GI disorders [20], there is an increasing interest in dietary strategies to modulate microbiota. For this reason, research has focused on the use of prebiotics, since many of these polysaccharides can be metabolized by intestinal microbiota, leading to the production of SCFAs (including acetate, butyrate, and propionate) [26].…”
Section: Mechanisms Of Action Of Prebioticsmentioning
confidence: 99%
“…In our study, the community structure of the gut microbiota was analyzed using T-RFLP, revealing that, at the phylum level, the population of Bacteroidetes was lower in the DSS + CD group than in both the DSS and normal groups. Although the differences were insignificant, a previous study showed that phylum distribution in IBD patients harbored significantly fewer Bacteroidetes than that in healthy subjects [70]. Furthermore, an inverse association has been reported between infection with C. difficile and abundance of Bacteroidetes [71].…”
Section: Discussionmentioning
confidence: 86%
“…In these experiments, we observed significantly higher enrichment of bacteria belonging to the family Ruminococcaceae and Lachnospiraceae in LXRα −/− mice compared to WT littermates in steady state, suggesting that lack of LXRα allows preferential colonization of specific groups of bacteria. Both Ruminococcaceae and Lachnospiraceae belong to the order Clostridiales and phylum Firmicutes and have been associated with multiple human diseases including IBD 22-24 and atherosclerosis 25,26 . While the abundance of both Ruminococcaceae and Lachnospiraceae are decreased in IBD patients, suggesting a protective role, they have been shown to be associated with pro-atherogenic effects.…”
Section: Discussionmentioning
confidence: 99%